Stydy on the characteristics and catalytic properties of Pt/SBA-15 in the selective oxidation of D-Glucose - Mai, Tran Thi Nhu; Thu, Nguyen Thi Minh; Trong, Pham Dinh; Ha, Nguyen Thi; Ly, Giang Thi Phuong (VNU Journal of Science: Natural Sciences and Technology, 2010)
Abstract